(untitled) (Research, Society and Development, 2021)
Objective: analyze the role of Primary Health Care (PHC), and its strategies to promote mental health of patients with psychological distress in the Covid-19 pandemic. Method: Integrative review, guided by the guiding question: What are the strategies for promoting mental health in Primary Health Care in the context of Covid-19, found in the Brazilian and international literature? Results/Discussion: For the present study, 10 articles were analyzed. The theme is addressed in different ways and points of view, and three topics can be highlighted: The impact of the pandemic by Covid-19 on mental health, the role of PHC in mental health care and its difficulties in the context of the Covid-19 pandemic and the strategies for promoting mental health in PHC in the context of the corona virus pandemic, where it is possible to observe how psychic suffering was present with social isolation, fear of death associated with Covid-19, domestic violence and political and economic insecurity, and how technology emerges as an important tool for promoting mental health. Conclusion: In an attempt to continue offering care to the population, new health promotion strategies were developed, such as the use of technology, despite different approaches, the effectiveness of the new methods and the importance of further studies addressing this theme were proven.